Continuity and change in ancient Umbrian cult places - Zapelloni Pavia, Arianna (Mnemosyne, 2025)
What difference did the Roman expansion make in the transformation of ancient Italy? With its conservative nature and abundance of material evidence, the religious sphere represents a unique lens through which we can study this process over time and across different sites. Tapping into the transformation of Italy as a result of Rome's expansion, this book problematizes the issue of Romanization and sheds light on the different processes of adaptation that occurred during the Roman conquest.--